Fabrication of syntactic foam fillers via integrated on/off-chip microfluidic methods for optimized geopolymer composites. Issue 4 (26th January 2022) - Wu, Hao; Ren, Yukun; Jiang, Tianyi; Wu, Wenlong; Lu, Yang; Jiang, Hongyuan
Abstract : A novel microfluidic expansion coupled thermal contraction method is proposed to optimize the fabrication of fillers and the corresponding composites. Abstract : To meet the evolving requirements of material designability, sustainability, and eco-friendliness, the development of syntactic foams puts great emphasis on filler optimization and matrix selection. Here, we present a novel microfluidic expansion coupled with the thermal contraction method to improve the fabrication of syntactic foam fillers (SFFs), highlighted by the independently regulated parameters in contrast to the hydrodynamic regulation approach. The eccentricity of droplets can be reduced via osmotic swelling under a hypotonic circumstance and further preserved through real-time UV polymerization. The eccentricity of shrunken SFFs after heat treatment is found to inherit the regulated configurations of droplets and this homogeneity difference of shell thickness can result in the mechanical performance deviation. Then, we choose greener material, geopolymer, as the binder matrix and prepare geopolymer syntactic foams (GSFs) by mold casting. The inclusion of SFFs has increased the atomic volume ratio of Si : Al in the matrix, thereby forming a strong interfacial bonding. The compressive yield strength of GSFs is inversely proportional to the volume fraction of SFFs, and the specimens after thermal exposure can still maintain their shape integrity and exhibit similar mechanical performance even with the formation of cracks. Moreover, the fire-resistant performance of GSFs has been visually validated by the combustion comparison experiment, characterized as flame retardancy, smoke-free, and basically intact morphology, which should give insights into the design and fabrication of functional composites.